Preventive Effect of Probiotics on Ventilator-Associated Pneumonia: A Meta-analysis of 2428 Patients. Issue 8 (August 2021) - Ji, Ting; Zhu, Xingxing; Shang, Futai; Zhang, Xiangcheng
Background: Researchers had contradictory conclusions about the role of probiotics in preventing ventilator-associated pneumonia (VAP), which has led to the controversial use of probiotics in mechanically ventilated patients. Objective: To explore the efficacy and safety of probiotics in preventing VAP. Methods: A literature search was conducted in 7 medical databases. Two investigators assessed literature quality independently and collected data. The primary outcome was the incidence of VAP. Secondary outcomes included 16 measures. Sensitivity analysis and subgroup and meta-regression analyses were performed to analyze the source of heterogeneity. P values <0.05 were considered statistically significant, and CIs were set at 95%. A random-effects model was set when I 2 <50%, otherwise a fixed-effects model was used. Results: A total of 20 randomized controlled studies with a total of 2428 patients were analyzed. Pooled results showed positive effects of probiotics on the reduction of VAP incidence (risk ratio [RR] = 0.672; P < 0.001; I 2 = 11.3%), length of ICU stay (WMD = −1.417; P = 0.012; I 2 = 90.7%), oropharyngeal (RR = 0.866; P = 0.031; I 2 = 12.4%) and gastric (RR = 0.645; P < 0.001; I 2 = 30.2%) colonization. Conclusions and Relevance: Probiotics can reduce the incidence of VAP and reduce oropharyngeal and gastric bacterial colonization. The results also suggest that probiotics do not cause adverse effects.